Creep and shrinkage prediction models for concrete water retaining structures in South Africa - Mucambe, Edson Silva David (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.